Sometimes Some Things Don’t (Really) Exist: Pragmatic Meinongism and the Referential Sub-Problem of Negative Existentials - Lenny Clapp (Crítica)
To solve the referential sub-problem of negative existentials one must explain why we interpret uses of, e.g., ‘Sherlock Holmes doesn’t exist’ as saying something coherent and intuitively true, even though the speaker purports to refer to something. Pragmatic Meinongism solves this problem by allowing ‘does not exist’ to be pragmatically modulated to express an inclusive sense under which it can be satisfied by something. I establish three points in defense of pragmatic Meinongism: (i) it is superior to Russell-inspired solutions; (ii) it is supported by independent evidence of pragmatic modulation; and (iii) it requires no dubious ontological commitments.